Perkembangan Tari Tanduak Tradisi Ke Tari Tanduak Kreasi Pada Sanggar Puti Junjung Kenagarian Sijunjung Kecamatan Sijunjung Kabupaten Sijunjung - Feby Try Rahmanda; Darmawati Darmawati; Indrayuda Indrayuda (SENDRATASIK UNP, 2019)
The research aimed to express, describe and analyze the development of The Development of Tanduak Traditional Dance to Tanduak Creation Dance at Puti Junjung Studio, Sijunjung District, Sijunjung Regency. The type of this research was qualitative research with descriptive analysis method. The object of this research was Tanduak Dance from Latang Village, Lubuak Tarok District, Sijunjung Regency. The types of data in this study were primary and secondary data. The main instrument was the researcher herself. Data collection techniques were carried out by means of literature review, observation, interviews, and documentation. The data collected were analyzed by interpretation techniques so that the truth could be obtained. The results showed that tanduak traditional dance had developed into tanduak dance that had been created.  This could be seen through the processing of motion, clothing, music, configuration, time and place of performances and aspects of dancers packed in a new form in Sijunjung. Then, a guidance and training were delivered by Puti Junjung Studio. In addition, it could be a place for young people in order to maintain the cultual heritage and the identity of the village.